Gender differences in surgical treatment of patients with cleft lip and palate. Issue 2 (4th March 2018) - Paganini, Anna; Hörfelt, Camilla; Mark, Hans
Abstract: Numerous gender-based differences in medical treatment have been recognized due to conscious or unconscious perceptions, i.e. gender bias. The aim of the present study was to investigate whether gender differences exist in the surgical treatment of patients with cleft lip and palate (CLP) anomalies. This study is a retrospective review of 235 consecutive patients with non-syndromic unilateral CLP or bilateral CLP born between 1966 and 1986. Each chart was reviewed, and 2178 surgical procedures were registered and categorized as primary surgery (primary lip, palatal and alveolar repair) or secondary surgery (aesthetic and functional revision). Different surgical procedures could be performed during the same surgical session. The number of surgeries performed was analysed and compared between genders. The results demonstrate that women with CLP received statistically significantly more secondary surgeries than men. No differences in the number of primary surgeries were identified. This study provides a gender perspective of the treatment of CLP. We identified no gender differences in primary surgery of the CLP. The standardized method of repairing the cleft is effective in preventing unjust treatment due to gender. However, we identified an indication of gender bias in cleft care regarding secondary surgeries of the nose and lip, namely, women are over-treated and/or men are under-treated. There are several possible explanations for this phenomenon, and further studies are needed.